Thunderbird Women - Fayant, Amanda (Septentrio Conference Series, 2019)
Indigenous gender roles have been distorted by colonialism, both through imposed systems of patriarchy and redefining gender roles within Indigenous communities. In Canada, the Indian Act of 1857 initiated a system of patriarchy which resulted in the loss of matrilineal family lines and Indigenous women’s rights to represent their community in leadership roles. This system still exists today, and despite numerous attempts to modify the law, the Indian Act still exerts patrilineal bias on Indigenous communities. In spite of this, there exists a large volume of research and literature by Indigenous women which investigates Indigenous feminism and the agency of Indigenous women in their communities. Examples include the writings of Sherry Farrell-Racette (Farrell-Racette 2010), Lee Maracle (Maracle 1996), Beverly Singer (Singer 2001) and Carol Rose Daniels (Daniels 2018) as well as online campaigns such as Rematriate (Rematriate 2018). Moreover, many Indigenous women in Canada are now stepping forward to address patriarchal systems in Indigenous institutions, such as the Assembly of First Nations, and outdated laws favouring male representation over female in meeting with governmental institutions. My research considers decolonization methods in relation to Indigenous feminist perspectives in research practice. Through an Indigenous research paradigm based on the teachings of the Indigenous Cree medicine wheel, this paper aims to decolonize homogenous forms of research by promoting Indigenous women’s knowledge. The medicine wheel in Indigenous teachings is a philosophy and a practical method of interpreting the physical, mental and transcendental domains. For research purposes, the medicine wheel offers a unique representation of Indigenous epistemology, ontology, axiology and methodology for use in research. Furthermore, following decolonial theory and Indigenous methodologies this research investigates the intersections of Indigenous feminism in decolonizing knowledge production and dismantling paternalistic affects in educational institutions. Including Indigenous approaches to listening, participation and storytelling as opposed to standardized interviews, as well as observation and document analysis, this thesis opens space for generating community-based definitions of Indigenous feminism. Focusing on the Canadian context, Indigenous women in Saskatchewan possess a vast amount of traditional knowledge and ways of knowing which have been devalued since the enforcement of the Indian Act. One vital way of Indigenizing cultural revitalization is by reclaiming Indigenous women’s epistemologies as a means of decolonizing gender roles and negating the impacts of the Indian Act.